Pemberian Leaflet Dan Penyuluhan Terhadap Peningkatan Pengetahuan Wanita Usia Subur Tentang Alat Kontrasepsi Kb - Chasanah, Siti Uswatun (STIKES Wira Husada Yogyakarta, 2014)
Background: Achievement of family planning participants in the Province of Yogyakarta Special Region in 2010 has reached as many as 50,876 of the estimated demand for new participants as many as 47 991 people in 2009, while the mens special new participants reached 4,638 participants from the public demand estimates as many as 10,174 new man. Implementation of the National Family Planning Program in Province of Yogyakarta Special Region successful in increasing the prevalence rate of 78.03 percent (in 2008) to 78.65 percent (in 2009) with the active participation of as many as 432,024 KB of couples of childbearing age for 549,313 inhabitants. Objective: To know the effect of leaflets and counseling to eligible women increased knowledge about family planning contraceptives. Methods: The study used a quasi experimental design with Static Group Comparison Design. Samples for groups of 30 samples and 30 leaflets for group counseling. Data analysis using a t-test. Results: Statistical test results obtained confidence level of 0.00 (p < 0.05) which showed no effect of extension leaflets and giving effect to the increase of knowledge about family planning to women of fertile age. The results of the calculation of the average obtained value-average before the extension before the extension after extension 32.3 and 29.0, while the average value before and after the administration of 27 leaflets leaflets giving 31.1 . Conclusions and Recommendations: there is the effect of leaflets and counseling to eligible women increased knowledge about family planning contraceptives. In line with the need of information about family planning for eligible women, in this study the extension needs to be enhanced so as to improve their knowledge of family planning acceptors and adjust spacing.